(untitled) (Journal of actual problems of jurisprudence, 2017)
The article deals with the modern understanding of civil society. Opens new interpretations of the data modern civil society by scientists from the legal point. The development of humanity man has lived and lives in society, society is divided into the following types of agricultural, stock, social, civil, etc. In these social relations there is nothing difficult in the development, as it is interconnected with the human factor in the face of citizens of a particular state. Depending on the development of public relations or that the above listed company may cease to exist or continue on. In the process of the development of society in a practical analysis of the data, some scientists formed the company rapidly and transiently stop the activity, ie in the form of legal entities cease and liquidate their activity and, for example, as a corporation, a limited liability company, etc. In any civil society institutions, the level of activity in the form of public associations is a kind of criterion of development, an indicator of the effectiveness of the democratic life in ideas. The special position of public associations as a product of organized independent initiative of the masses due to several factors as an indispensable channel of social experiments in the areas that affect the building of civil society. Formation of civil society actualizes in the public consciousness of the population of Kazakhstan ideals of democratic and legal state. The ideology of an open civil society based on the mutual recognition of the priorities of the human rights and interests of all civil institutions. Their implementation will contribute to strengthening public understanding and consent. In this case, the most appropriate form provided by the coordination of civil society interests and improving the efficiency of public policy. Key words: society, civil society, citizen, ideology, human right, particular state, development, democratic, area, legal state.